Study on the Impact of Drainage Noise in Residential Bathrooms Based on Finite Element Simulation - WANG, Yaping; DENG, Xin; CHI, Bingyuan; CUI, Yanqiu (Archives of Acoustics, 2024)
Residential bathroom drainage noise is a primary source of indoor noise that directly affects quality of life and physical and mental health. Therefore, based on the acoustic theory and the finite element simulation technology, this paper proposes a method to simulate the drainage noise characteristics and its impact range jointly using the flow and acoustic fields. The pressure at the pipe wall caused by the internal flow field of the bathroom drainage pipe is calculated by the Fluent software. Simulations are carried out with the Virtual Lab software to predict the drainage noise characteristics and spatial distribution and to analyse the influence of factors such as the door position, riser position, and the partition wall material on the noise distribution. The results show that drainage noise has prominent high-frequency characteristics, the position of the bathroom drainage pipes and doors affects the spatial noise distribution, and the sound insulation performance of a partition wall with ordinary fired bricks in the bathroom is slightly better than that of ordinary concrete bricks, lightweight aggregate concrete blocks or fly ash blocks. This paper provides a theoretical basis and practical reference for reducing the impact of residential drainage noise and creating a healthy and comfortable indoor acoustic environment.